MAIN STAGES OF MINING DEVELOPMENT IN RUSSIA (ON THE 300TH ANNIVERSARY OF THE RUSSIAN GEOLOGICAL AND MINING SURVEY) - Gatinsky Yu.G.; Vishnevskaya N.A. (My University, 2001)
The mineral resources of Russia grew with the territorial expansion of the country; new frontiers gave Russia access to new mineral sources, which enhanced the independence of the Russian economy. The exposition devoted to the 300th anniversary of the Russian Geological and Mining Survey took place at the Vernadsky State Geological Museum in September 2000. Materials displayed there allowed one to trace the development of Russian mining from the first pioneer expeditions to the modern mining industry, which has made Russia one of world leaders in resources and mining of strategic materials.